A New Global Regulation on Public Health â€“ Is the World Ready for A Second Treaty? - I Nyoman Putu Budiartha; Rahmat Mohamad (Sociological Jurisprudence Journal, 2022)
The World Health Organization (WHO) declared novel coronavirus (COVID-19) as a worldwide pandemic that has caused in high number of deaths in many countries and across national boundaries. In its early stage, governments all over the world have decided to implement lockdowns and closing of national border as ad hoc measures to slow down the drastic increase of the widespread of Covid-19. The United Nations through the UN General Assembly at its 74th session adopted Resolution on Global solidarity to fight COVID-19 recognized that this pandemic requires a global response based on unity, solidarity and renewed multilateral cooperation. The UN General Assembly passed under resolution on international cooperation to ensure global access to medicines, vaccines and medical equipment to face Covid-19 pandemic. This article is divided into three parts; the background of the current health security regulatory system under the International Health Regulations (IHR) 2005; the pursuance of pandemic treaty sponsored by WHO and 26 countries from Europe, Latin America and Asia and its justifications and the challenges ahead in resolving world pandemic regulatory system. The IHR aims for international collaboration "to prevent, protect against, control, and provide a public health response to the international spread of disease in ways that are commensurate with and restricted to public health risks and that avoid unnecessary interference with international traffic and tradeâ€. There is a need to design a compulsory mechanism for alert to act much earlier and the alert system must be a build in compulsory mechanism. The compliance can only be made possible through the availability of coordination platform between WHO and other international organization like IMO, WTO and ICAO. Thirdly, United Nations General Assembly (UNGA) must play the vital role in giving the mandate to WHO to implement the coordination with other international organization. Hence, member states must therefore, give their political commitment in ensuring the successful coordination with other international agencies.